Relational contracting and its combination with the BIM methodology in mitigating asymmetric information problems in construction projects - Marinho, António; Couto, João; Teixeira, José (Journal of Civil Engineering and Management, 2021)
Project management in the construction sector is a complex and uncertain process and companies tend to look for the lowest value in the procurement of services and materials. However, contractors do not share the necessary information with the contracted parties and thus give rise to the asymmetric information (AI) phenomenon. The aim of this study is to perform an analysis of the determining factors in the adoption of relational contracting (RC) in combination with Building Information Modelling (BIM) to reduce AI. The results of a questionnaire survey, which was e-mailed to 14 specialists with solid experience (over twenty years) and knowledge in construction projects, revealed that the probability of the AI phenomenon occurring in Portugal is very high, and its impact on construction projects is equally high. The results also show that RC in combination with the BIM methodology contributes very positively to the mitigation of AI problems in construction projects in Portugal. Approximately 85% of respondents consider that the government should seek to reduce AI in the public works sector through the use of RC and its combination with the BIM methodology in the Portuguese Public Contracts Code.